Do health-brand fan pages satisfy their consumers' desires?. (19th October 2021) - Castillo, Gricel; Carrete, Lorena; Arroyo, Pilar
Brand fan pages offer an opportunity to collect information from consumers and enhance customer engagement. This study explores the gratifications sought by consumers of healthy food brands when they participate in these platforms. A qualitative approach was used to collect information in the fortified ready-to-eat cereals category. Data were collected via in-depth interviews followed by a netnography study to analyse the informational, entertaining, relational, and remunerative gratifications provided by health-brand fan pages and the shortcomings perceived about the same. Based on the findings, a conceptual model that enhances the understanding of what are the consumer interaction determinants with brand fan pages is provided. Several studies have applied the uses and gratification theory to explain why consumers are motivated to use social media. However, this study is the first to explore the gratifications offered by health-brand fan pages.